Two new species of Digamasellidae from Taiwan (Acari: Mesostigmata) - Ma, Li-Ming; Ho, Chyi-Chen; Wang, Shun-Cheng (Zootaxa, 2014)
This paper reports the occurrence of two new species of Digamasellidae from Taiwan, Dendroseius vulgaris n. sp. and Dendrolaelaps (Foveodendrolaelaps) linjianzheni n. sp. Dendroseius vulgaris is described based on the morphology of adult females, adult males and deutonymph, and D. linjianzheni is based on the morphology of adult females and males. This is the first report on the mite species of Digamasellidae from Taiwan.